KONSEP DAN DATA MODEL APLIKASI LELANG KOMODITAS PERTANIAN BERBASIS ANDROID - Awaludin Abid (LP3M Universitas Putra Bangsa, 2023)
Concept and data model of application can be implemented in the Auction sector, especially for agricultural commodities. The main benefit for farmers is to increase income because it expands market segmentation,for governments to monitor the pace and development of agriculture in an area. The application is designed in android system,that has high mobility so it is easy to use anywhere as long as it has an internet network, the addition of a price check facility from auction results in the application is expected to add information to farmers and buyers in order to reduce disinformation about the price of an agricultural commodity.